Impact of FDI on Economic Growth in South Asia: Does Nature of FDI Matters?**This article is an outcome of a project supported by South Asia Network of Economic Research Institutes under 16th RRC. (August 2020) - Chaudhury, Saswata; Nanda, Nitya; Tyagi, Bhawna
Foreign direct investment (FDI) is believed to be an important determinant of economic growth in developing countries, but its impact varies across countries. Presence of other determinants (like domestic investment, inflation, infrastructure and external trade) may augment or retard the potential impact of FDI on economic growth. Moreover, due to the non-homogeneous nature of sectoral FDI, the sectoral composition may create differential impact on economic growth. Hence, it is necessary to identify and measure the differential impact of sector-wise (primary versus secondary versus tertiary sector) FDI inflow. Exploring the nature and behaviour of overall and sectoral FDI inflow in South Asian countries in the recent past, this article has taken a holistic approach in studying and analysing the FDI-growth dynamics. The study found that the impacts of FDI in South Asia are indeed influenced by sectoral composition of FDI.